The Florida Scrub-Jay: A Species in Peril - Steve A. Johnson; Karl E. Miller; Travis Blunden (EDIS)
WEC-261, a 6-page illustrated fact sheet by Steve A. Johnson, Karl E. Miller, and Travis Blunden, provides biological information about the Florida Scrub-Jay and the unique habitat it depends on for survival. It also includes advice for how people can help conserve this unique and imperiled bird. Published by the UF Department of Wildlife Ecology and Conservation, June 2009.